Hipertensi pada wanita menopause; Sebuah tinjauan literatur - Lestari, Ayu Dwi; Putri, Riska Hediya; Yunitasari, Eva (Wellness And Healthy Magazine, 2020)
Menopause is the cessation of menstrual cycles in women, the condition of menopause inevitably faced in the life of one woman and a natural process in line with age. Menopause is not a disease or abnormality, menopause occurs at the end of the last menstrual cycle, but the ability is newly acquired if a woman has not experienced her menstruation cycle for at least 12 months, one of the consequences of menopause is a decrease in estrogen hormones and occurs increase in cortisol hormones so that the menopause women tend to be more stressful that can affect the increase in blood pressure or Literature Studies Review a variety of study outcomes on those in naturally menopausal women and may result in hypertension. This Literature review uses a critical review of the full-text article in the last five years that is from 2015-2020 in Bahasa Indonesia and English that meets the criteria of PICO and SPIDER. Search database through Google Scholar, National Library of the Republic of Indonesia, PubMed, Proquest with the keyword; menopause, perimenopause, Hypertension caused by menopause, to get articles that fit the topic and purpose. Further intensified article readings and a summary of each article. In the time of menopause often occurs hypertension in the results of physical activity with exercise yoga and aerobic gymnastics so as not to stress on menopause so as not to cause hypertension, eating healthy foods like the Kedalai watermelon juice can also lower blood pressure and do not make stress on menopause mother. This literature study can be used as a source of information to conduct research related problems of the menopause period